PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII.3 di SMP NEGERI 32 PEKANBARU - Desta Simarmata; Suarman Suarman; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve improve social studies learning outcomes of students in class VII.3 in Pekanbaru State Middle School 32 by using the scramble learning model. The method used in this study is the Class Action Research Method (CAR). The results of the study obtained from teacher activities in the first cycle were 21 (75%) categorized as good and increased in the second cycle to 27 (96.42%) categorized as very good. The category of student activity in the first cycle was 23 (82.14%) categorized as very good then increased in the second cycle to 29 (96.85%) categorized as very good. The increase in learning outcomes from the basic score to the first cycle is 3.7% and the increase in learning outcomes from the base cycle of the second cycle is 8.275%. Classical learning outcomes on basic scores that reach KKm only 72.5% experienced an increase in the first cycle to 80% and in the second cycle increased again to 85%. The conclusion that the use of the scramble learning model can improve social studies learning outcomes of students in class VII.3 Pekanbaru 32 Middle School.Key Words: Scramble Learning Model, Scramble Learning Model